2016
DOI: 10.31436/iiumej.v17i2.610
|View full text |Cite
|
Sign up to set email alerts
|

Co-Production of Lactic Acid and Ethanol Using Rhizopus Sp. From Hydrolyzed Inedible Cassava Starch and Leaves

Abstract: Production of lactic acid and ethanol from inedible cassava starch and leaves was investigated. Prior to fermentation, hydrolysis of the starch and leaves was conducted. Hydrolysis was optimized by manipulating at three levels each four particular factors, namely acid concentration, starch concentration, temperature, and reaction time. Maximum glucose yield of 0.96 g/g was obtained when 2.5% (w/v) of cassava leaves with 2.5% (w/v) of starch was hydrolyzed using 0.20 M of nitric acid at 160oC of temperature for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Rhizopus sp. was previously isolated from ragi tapai and grown on potato dextrose agar (PDA) under an incubation temperature of 37°C for 7 days [14]. After growth and sporulation, 15 ml distilled water was added to each agar plate, which was then scratched to release spores.…”
Section: Microorganism and Inoculum Preparationmentioning
confidence: 99%
“…Rhizopus sp. was previously isolated from ragi tapai and grown on potato dextrose agar (PDA) under an incubation temperature of 37°C for 7 days [14]. After growth and sporulation, 15 ml distilled water was added to each agar plate, which was then scratched to release spores.…”
Section: Microorganism and Inoculum Preparationmentioning
confidence: 99%
“…Kemampuan hidrolisis pati secara kimiawi dengan HCl sangat rendah. Pada penelitian Azmi et al (2016), pati dihidrolisis dengan asam menggunakan suhu 160℃ agar menghasilkan produk/gula pereduksi yang tinggi. Sementara pada percobaan ini, pati dengan campuran HCl diinkubasi pada suhu 100℃.…”
Section: Hasil Dan Pembahasanunclassified
“…The fungi usually cultivated in the inoculum such as R. oligosporus, R. oryzae, R. stolonifer, and R. arrhizus [9]. Some works reported that R.oryzae and R.oligosporus could utilize various agricultural residues such as L-LA, fumaric acid, and ethanol to produce LA [10,11]. The use of Rhizopus has several advantages; it can suppress downstream processes because of the ease of separating mould filaments.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Rhizopus has several advantages; it can suppress downstream processes because of the ease of separating mould filaments. Previous researchers have studied LA fermentation using strain Rhizopus sp, with different carbon sources, nitrogen sources, and operating conditions (pH, temperature, volume, and rotation speed) but mostly using acid hydrolysis to convert polysaccharides into monosaccharides [10][11][12]. Acid hydrolysis has drawbacks such as corrosion-resistant tools, carbohydrate degradation and product recombination [8].…”
Section: Introductionmentioning
confidence: 99%